Management of Acacia Plantations for Charcoal Production: Local Economies and Sustainability - Dafa-Alla, Dafa-Alla Mohamed; Abidallha, Eltayib H.M.A. (University of Khartoum Journal of Agricultural Sciences, 2023)
The objectives of this research were to estimate volume of charcoal produced per unit area of Acacia seyal plantations at Wadelbashier Forest Reserve and to estimate financial profitability (US ha-1 ) of charcoal production, using net present value (NPV) as a decision criterion. Data on tree growth was collected, using fixed-radius temporary circular sample plots. Present and harvest age standing wood volumes were estimated. Market-related data were collected through structured interviews of key informants of the staff of Forest National Corporation (FNC) of Algadarif State, members of Trade Union of Fuelwood Producers and Traders, and from secondary sources of the state forestry service. The results indicated that the present standing wood volume (m3 ha-1 ) ranged between 8.4 and 26.2 and that charcoal production from A. seyal plantations managed for a rotation of 20 years at 12% annual discount rate yielded a negative mean financial NPV of US ha-1 -30.3 indicating that charcoal production at current stocking, factor costs, output prices, a 12% annual discount rate and a rotation length of 20 years is not financially profitable. The study concludes that policy and management interventions are inevitable for sustainable production.